An Investigation Into Food Neophobia and Cultural Intelligence: Evidence From Business Classes (Journal of Organizational Psychology, 2022)
This study investigated the relationship between food neophobia, the tendency to avoid new foods, and cultural intelligence (CQ). A questionnaire was administered to undergraduate students at a university in the Northwestern United States. Survey administration occurred during the 2018-2019 academic year. The questionnaire included a combination of demographic questions along with two validated survey instruments, the Cultural Intelligence Scale (CQS) (Ang & Dyne, 2008) and the Food Neophobia Scale (FNS) (Pliner & Hobden, 1992). CQS was used to measure cultural intelligence and FNS gauged food neophobia. Results indicated a strong correlation between CQ and food neophobia. An analysis of CQ’s components showed that the significant drivers of the results were metacognitive/strategy and motivational/drive CQ subconstructs.
Keywords: organizational psychology; cultural intelligence; food-neophobia; diversity and inclusion; higher education; business